Spiritualitas Petugas Pastoral dalam Karya Pelayanan Pastoral Awam - Sitepanus Zebua; Bartolomeus Sihite; Yuadi Gaho (Journal New Light, 2024)
Spirituality is fundamental in the life of pastoral workers. Because spirituality is the main driving force that gives enthusiasm to a pastoral officer, especially in ministry. The service of a pastoral officer is very meaningful if it is accompanied by a person who is brave, enthusiastic and humble, because the duty and war of a pastoral officer is to proclaim the Word of God. Basically, pastoral officers are called and sent by Christ to proclaim the Word of God to all believers with the aim of saving them. Lay Pastoral Officers are Christian believers who have received baptism and been anointed with the Holy Spirit. Through the baptism they have received, lay pastoral officers become members of the Body of Christ, gathered into the People of God, by carrying out the Tri-task of Christ according to their ability to carry out their mission for all Christians in the Church and the world. Lay pastoral officers live in the world, meaning carrying out worldly duties and work, and being in the midst of the realities of family and social life. They are called by God to carry out their own duties by imbuing the spirit of the Gospel, in that way they radiate faith, hope and love, especially the testimony of life. Lay pastoral officers who carry out the Tri-tasks of Christ, one of which is as preachers of the Word of God, strive to develop the faith of Catholics according to the values ​​of the Kingdom of God.